An Analysis of Politeness Strategy Done by North Koreans Seen in “My Brothers And Sisters in the North” Documentary - Handayani, Widi (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
It is a study on politeness strategy proposed by Brown and Levinson (1987). It focuses on the utterances spoken by North Koreans. Negative and positive politeness strategy are found in the study. North Koreans perform negative politeness when dealing with the things related to works or their leaders. It shows by the use of the word “please” to give a command, pronoun “we” to indicate exclusiveness which exclude the host as a person comes from different land, pronoun “our” to show their possession towards a particular things, and the use of specific names to refer to their leaders. It is applied to present their professionalism towards their works and loyalty to their leaders. It aims to create distant to people outside the country in dealing anything related to the nation. Positive politeness is used to reveal their solidarity towards the host. It indicates that they share the same origin and personalities. It functions to convey their feelings to the host towards particular things. Telling their feelings to people from different place suggests that they trust the host and want her to understand them. It gives an affirmation that even they live in isolation, they can be close to people they barely meet.